Viabilidade de uso de cordoalha de aço CP-210 RB em viga pré-moldada para pontes - Migliore, Gabriel Moreira (Universidade Federal de São Carlos, 2018)
This work aims to document the production process and characteristics of the new Brazilian prestressing steel CP-210 RB, as well as evaluating its use viability and to indicate design guidelines for the application in the design of precast prestressed concrete beam bridges. In this thesis, numerical examples of the design of isostatic reinforced beam are presented considering the use of conventional passive reinforcement and prestessed concrete using either CP-190 RB and CP-210 RB steels. Design procedures consider both full and limited prestessing specifications. Typical, design details are also considered. Comparative studies of materials and execution procedures are considered assessing the bridge deck, designed with several girder beams, for execution of the prestressed or reinforced precast beams. The number of girders and the deck width were determined according to the DER-SP specification for road bridges and overpasses. The beam height varies according to the span length. Designs assessed both the Service Limit State and the Ultimate Limit State considering each construction system. From the analysis results, trend lines were determined indicating the class 450 isostatic precast beams for road bridges production cost, with deck width of 14 m and nominal length from 20 to 35 m, considering solutions in reinforced concrete and CP-190 RB and CP-210 RB prestressed concrete options. With the trend lines, it was possible to determine that bridge or overpass for deck structure with lengths greater than 22 m are economically viable with the use of precast prestressed girders using the new Brazilian CP-210 RB steel. This work also presents, for each chosen construction system, the equations to determine the production cost of precast girder as a function of the nominal length of the deck structure and according to the production items unit costs: concrete, formwork, CA-50 steel, CP-190 steel, CP-210 steel and anchorages. The results show that the anchorage cost represents about 15% to 20% of the total production cost of the prestressed beam, beings this cost higher than the concrete and formwork costs in the case of full prestressing. The relative cost of the anchorage decreases with increasing the nominal length of the deck structure.
Viability of using CP-210 RB steel strand in precast girder bridges
Keywords: Concreto protendido; Aço CP-210; Longarina pré-moldada; Pontes; Prestressed concrete; Grade 300 steel strand; Precast girder; Bridges; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL; ENGENHARIAS::ENGENHARIA CIVIL::ESTRUTURAS